The electrocardiogram of anaesthetized southern sea lion (Otaria flavescens) females - Dassis, Mariela (2016)
Objectives The goal of this study was to characterize for the first time the electrocardiogram (ECG) of the southern sea lion (SSL) Otaria flavescens. Animals, materials and methods Thirteen wild SSL females were captured at Isla de Lobos (Uruguay) and anaesthetized with isoflurane. Electrocardiographic recording was performed on anaesthetized animals at ventral recumbence following standardized procedures. Results The ECG recordings showed normal sinus rhythm. Amplitude and duration of P and T waves, QRS complex, PR interval, QT interval and ST segment (STS) were determined for all animals in all leads. QT corrected was determined in lead II. P wave polarity was consistent among animals (positive in LI, LII, LIII and AVF leads and negative in AVL and AVR leads for all animals), but T wave polarity did not present any constant pattern among animals, being either positive, negative or biphasic in different leads and different animals. The PR interval (0.15 ± 0.2 s) was similar to the allometric prediction for most of mammalian species including humans. The STS were normal in 10 of the SSL but showed STS depression in three of the animals. Almost all animals had a negative electrical axis (-30° to -120°), with one exception that showed a positive electrical axis (120°). Mean eupnoeic heart rate was 104.61 ± 10.06 (range = 88-120) beats per minute. Conclusions This study was the first ECG description for this species, and provides valuable information for cardiac monitoring during anaesthesia.